Physical, biochemical, and neuromuscular responses to repeated sprint exercise in eumenorrheic female handball players: effect of menstrual cycle phases - Graja, A.; Kacem, M.; Hammouda, O.; Borji, R.; Bouzid, M. A.; Souissi, N.; Rebai, H. (The Journal of Strength and Conditioning Research, 2022)
Very few studies have been interested in the relationship between ovarian hormones and physiological function in female athletes. The aim of this study was to assess the effect of menstrual phases (MP) on physical, neuromuscular, and biochemical responses after repeated sprint exercise (RSE) in female handball players. Ten eumenorrheic athletes (22.5 ± 1.5 years, 1.70 ± 0.04 m) participated in 3 study visits (follicular phase [FP], luteal phase [LP], and premenstrual phase [PMP]). During each MP, they performed 20 × 5-second cycle sprints interspersed with 25 seconds of rest. Maximal voluntary contraction (MVC) tests of the knee extensor muscles at 90° of knee flexion were performed before and after RSE. Peak force and electromyography (EMG) signals were measured during the MVC tests. Blood samples were collected before and 3 minutes after each session. The percentage of decrement in peak power output over the 20 × 5-second cycle test (i.e., fatigue index) calculated between sprints 1 and 20 decreased significantly during PMP (-43.3% ± 5.7%) but not in LP (-39.2% ± 7.7%) compared with FP (-32.44% ± 6.3%) (p < 0.05). Moreover, no significant difference was found between MP in all frequency components of EMG before RSE (p > 0.05). Maximal voluntary contraction, neuromuscular efficiency, and median frequency values of vastus lateralis and rectus femoris were significantly decreased in PMP compared with FP and LP (p < 0.05). Creatine kinase (CK) levels were significantly higher in PMP compared with FP and LP after RSE (p < 0.05). These findings suggest that RSE induces more peripheral fatigue associated with muscle damage in PMP. This might be attributable to hormonal variation across MP. Therefore, FP seems to be the right time for intense training to improve strength performance.